From sacred spaces to imperial glory: a deconstruction of civilizational discourses in Türkiye and Saudi Arabia - Oztig, Lacin Idil; Ermihan, Erman (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This study employs narrative analysis to compare and critically examine the civilizational discourses of T & uuml;rkiye and Saudi Arabia. T & uuml;rkiye promotes an Ottoman-Islamist vision, casting its imperial heritage as a guarantor of regional leadership and an alternative to the Western-led international order. In contrast, Saudi Arabia grounds its legitimacy and its regional leadership aspirations in its sacred geography as the birthplace of Islam and Custodian of the Two Holy Mosques. The analysis shows that both states adopt power-oriented and reductionist approaches to civilization, albeit through divergent modalities. While T & uuml;rkiye utilizes an 'imperial register', evoking the grandeur of empire building, Saudi Arabia adopts a 'sacred-spatial register', framing itself as the spiritual center of the Islamic world. These divergent modalities expose the spatio-temporal fixities embedded in contemporary civilizational discourses. By proposing a new conceptual axis for understanding intra-civilizational variation, this study offers novel insights into civilizational analysis and key debates in International Relations.
Keywords: Civilizational discourse; populism; foreign policy; T & uuml; rkiye; Saudi Arabia; neo-ottomanism; POLICY; NARRATIVES; CLASH; CONSTRUCTIVISM; POWERS; International Relations; Social Sciences - Other Topics